# Answer to Question #22665 in Algebra for clarkie

Question #22665

If possible, completely factor the expression. (if the expression is not factorable, enter NF.)

x^2 - 8x - 9

x^2 - 8x - 9

Expert's answer

x^2 - 8x - 9 = x^2 + x - x - 8x - 9 = x^2+ x -9x - 9 =

=x(x+1) - 9(x+1) = (x-9)*(x+1)

Answer: (x-9)*(x+1)

=x(x+1) - 9(x+1) = (x-9)*(x+1)

Answer: (x-9)*(x+1)

Need a fast expert's response?

Submit orderand get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

## Comments

## Leave a comment